The Latent Structure of Loneliness: Testing Competing Factor Models of the UCLA Loneliness Scale in a Large Adolescent Sample. (April 2015) - Shevlin, Mark; Murphy, Siobhan; Murphy, Jamie
This study assessed the dimensional structure of the UCLA Loneliness Scale ([UCLA-LS], UCLA-3). Data from the Northern Ireland Young Life and Times Survey (2011), a survey of 1, 434 16-year-olds, was used to examine the underlying factor structure of the scale. Confirmatory factor analysis was employed to compare alternative factor analytical models that can inform the scoring of the measure and determine the degree to which different factors provided unique predictive utility. Fit statistics indicated that the best fitting model comprised three correlated factors: Isolation, Related Connectedness, and Collective Connectedness. These findings were consistent with previous findings that identified the multidimensional nature of the UCLA-LS. The study also found evidence that the subscales were differentially associated with psychiatric morbidity as measured by the General Health Questionnaire (GHQ-12) and provides a more reliable and comprehensive framework to assess the clinical significance of loneliness.